Inefficient magnetic-field amplification in supersonic laser-plasma turbulence - Bott, AFA; Chen, L; Boutoux, G; Caillaud, T; Duval, A; Koenig, M; Khiar, B; Lantuéjoul, I; Le-Deroff, L; Reville, B; Rosch, R; Ryu, D; et al. (American Physical Society, 2021)
We report a laser-plasma experiment that was carried out at the LMJ-PETAL facility and realized the first magnetized, turbulent, supersonic plasma with a large magnetic Reynolds number ($Rm ≈ 45$) in the laboratory. Initial seed magnetic fields were amplified, but only moderately so, and did not become dynamically significant. A notable absence of magnetic energy at scales smaller than the outer scale of the turbulent cascade was also observed. Our results support the notion that moderately supersonic, low-magnetic-Prandtl-number plasma turbulence is inefficient at amplifying magnetic fields.